2010
DOI: 10.1371/journal.pgen.1001077
|View full text |Cite
|
Sign up to set email alerts
|

An Alpha-Catulin Homologue Controls Neuromuscular Function through Localization of the Dystrophin Complex and BK Channels in Caenorhabditis elegans

Abstract: The large conductance, voltage- and calcium-dependent potassium (BK) channel serves as a major negative feedback regulator of calcium-mediated physiological processes and has been implicated in muscle dysfunction and neurological disorders. In addition to membrane depolarization, activation of the BK channel requires a rise in cytosolic calcium. Localization of the BK channel near calcium channels is therefore critical for its function. In a genetic screen designed to isolate novel regulators of the Caenorhabd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…In these transgenic animals, we investigated the localization pattern of CTN-1 in muscle. We previously reported that CTN-1 and SLO-1 appear as puncta near dense bodies (16). Consistent with this report, the full-length CTN-1 exhibits a punctate pattern at the muscle membrane (Fig.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In these transgenic animals, we investigated the localization pattern of CTN-1 in muscle. We previously reported that CTN-1 and SLO-1 appear as puncta near dense bodies (16). Consistent with this report, the full-length CTN-1 exhibits a punctate pattern at the muscle membrane (Fig.…”
Section: Resultssupporting
confidence: 90%
“…This transgene rescues the headbending phenotype, indicating that CTN-1 localization in these transgenic animals reflects its normal in vivo localization. In wild-type animals CTN-1::GFP shows a punctate pattern as we reported previously (16). However, in both dys-1 and dyb-1 mutants, the punctate pattern of CTN-1::GFP disappeared (Fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations